Creative teacher's dictionary: Enhancing teacher competence in creating learning media to support Indonesia's SDGs program - Dea Febrina Irawan; Adilla Dzakiroh; Diva Ayu Putri Pradana; Dwi Antika Andi Saputri; Faisal Sadam Murron (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
This research focuses on the Creative Teacher's Dictionary, specially designed for educators to assist in developing digital learning media that support Indonesia's Sustainable Development Goals (SDGs) program. This dictionary is crucial in shaping high-quality educators capable of providing meaningful learning experiences. The research is guided by selecting a dictionary as the primary tool for developing educational media because a dictionary plays a strategic role in providing comprehensive guidance to educators in designing learning media that support SDGs. The Creative Teacher's Dictionary offers practical guidance on using various up-to-date applications and technologies to create innovative and relevant learning experiences. This research aims to develop the Creative Teacher's Dictionary, provide comprehensive resources for educators, and ensure the quality of its content. The research employs the Design and Development (DD) method using the ADDIE model. The assessment involves expert validation and interviews to ensure the quality of the content of the Creative Teacher's Dictionary. The validation results by subject matter experts and language experts indicate an